Neither Here nor There: Exploring the Transnational Identity of West African Migrants living in South Africa - Opara, Ijeoma (Department of Political Studies, 2021)
Transnationalism as a theory has explained the causal nature of migration over time, against the backdrop of an ever-changing globalised world. The movement of people and their motivating factors have been deeply researched within migration literature and other surrounding fields. However, the intricacies of transnationalism among migrants have remained fairly unexplored, with little being written specifically on the topic of intersecting identities and othering experienced by transnational migrants. In South Africa, xenophobia has been a strong issue connected to migrants, whereby those from other African countries face discrimination based on their nationality, ethnicity, and economic disparities. However, there is a dearth in understanding how othering as a concept manifests beyond the overt forms of violence, and how it links to systemic forms of exclusion. The term ‘West-a-phobia' explores a more specific phenomenon of xenophobia, whereby West African migrants living in South Africa face discrimination based on specific national, cultural, and economic characteristics of their identity. By using this concept, and by providing the historical context of othering, this dissertation explores transnational identities through unpacking concepts such as ‘othering', ‘transnationalism', ‘identity', and critiquing the nationstate. A qualitative approach was implemented by interviewing six respondents residing in Cape Town and Stellenbosch, South Africa. Respondents' contributions were collected via online response sheets and face-to-face interviews from August to November 2019. This was followed by critical analysis and concluded with evidence-based nuances surrounding the intersecting tenets of the aforementioned concepts. The key findings from this study conclude that West African migrants that have lived in South Africa over a certain period of time experience a lack of cohesion and integration into society. This takes place through processes of othering through physical differentiation and cultural characteristics. Furthermore, West African migrants maintain a connection to their country of origin through engaging in what Crush and MacDonald (2000) characterises as transnational activities. Finally, this study concludes that there are stratified layers to the conceptualisation of citizenship, and that the qualitative research done corroborates with certain aspects of transnationalism theory.